2016
DOI: 10.1088/1748-6041/11/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cell-enhanced osteogenic differentiation by contact interaction with polyethylene terephthalate nanogratings

Abstract: Among the very large number of polymeric materials that have been proposed in the field of orthopedics, polyethylene terephthalate (PET) is one of the most attractive thanks to its flexibility, thermal resistance, mechanical strength and durability. Several studies have been proposed that interface nano- or micro-structured surfaces with mesenchymal stromal cells (MSCs), demonstrating the potential of this technology for promoting osteogenesis. All these studies were carried out on biomaterials other than PET,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…To overcome the problem of the LARS ligament's osteointegration, several authors worked in the last years to enhance the biologic fixation of the graft using nanotechnologies. 23 24 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…To overcome the problem of the LARS ligament's osteointegration, several authors worked in the last years to enhance the biologic fixation of the graft using nanotechnologies. 23 24 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the studies was conducted with bone marrow derived mesenchymal stromal cells (BM-MSCs). Very recently our group demonstrated that nanogratings, alternate lines of sub-micrometer sized ridges and grooves, can effectively polarize BM-MSCs by pure contact interaction (Antonini et al, 2014), and promote enhanced osteo-differentiation with respect to flat surfaces (Antonini et al, 2016). There is indeed a large consensus considering BM-MSCs as the progenitors of the skeletal tissue related cell lineages for their ability to differentiate into adipocytes, osteoblasts and chondroblasts (Keating, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The use of specific biomaterials has demonstrated significant improvement in MSC therapy. Antonini et al (2016) showed that the use of polyethylene terephthalate nanogratings improved the osteogenic differentiation of MSCs.…”
Section: Three-dimensional Culture Of Mesenchymal Stem/stromal Cellsmentioning
confidence: 99%